Common Ownership, Executive Compensation, and Product Market Competition - Bloomfield, Matthew J.; Friedman, Henry L.; Kim, Hwa Young (The Accounting Review, 2024)
ABSTRACT The negative effects of common ownership on competition have received significant attention, but many proposed mechanisms for institutional investor influence seem implausible. We develop and test an analytical model of optimal compensation in an oligopoly with common ownership, focusing on revenue-based pay as a plausible channel through which institutional investors might influence competition. Our model implies a negative effect of common ownership on firms’ use of revenue-based pay. Using both associative analyses and an event study difference-in-differences design based on plausibly exogenous institutional mergers, we find no evidence of a negative relation between common ownership and the use of revenue-based pay, except in an economically small subsample of extremely concentrated owners. Results involving relative performance incentives are similar. Collectively, our results provide no support for the notion that cross-owning blockholders in general influence compensation contracts in order to soften executives’ incentives to compete aggressively. Data Availability: Data are available from the public sources cited in the text. JEL Classifications: D43; G30; L13; M12; M40; M52.